Morphological and molecular diagnosis of fungi associated with two species of carp (Cyprinus carpio) and shank (Tilapia sp.( in Karbala / Iraq - Zeinab A.M. Al-tememe; Faezah Hamad Almasoudy; Asmaa Mansour Al-Hakeem; Noor sabah (Zien Journals, 2022)
The aimed of study was identifying the fungi associated two types of fish, carp (Cyprinus carpio) and the shank (Tilapia sp.) from freshwater fish in Karbala / Iraq. The isolates from all body regions of the fish revealed three types of fungi, Lichtheimia corymbifera with a percentage of The frequency was 20% and Aspergillus terreus and Aspergillus niger had a frequency of 50 and 40% respectively .The morphologically isolated fungi were diagnosed using the approved taxonomic keys, the diagnosis was confirmed by polymerase chain reaction (PCR) technique.
Keywords: Cyprinus carpio; Tilapia sp; Lichtheimia; PCR